Saenal School in South Korea: Its Historical Significance - Park, Yong-Ho; Kim, Kang-Hyun; Jeong, Moo-jin; Kim, Ho-Woog; Chung, Jun-Ki (Journal of Education Culture and Society, 2024)
Aim. The importance of this study lies in the fact that in contemporary South Korean society, a model of multicultural education is unquestionably required for the offspring of Goryeoin (Koreans), who were dispersed across Russia, Ukraine, and Central Asia before settling in their homeland of Korea because they urgently need to restore their healthy identity.Method. The basic methods of investigation are historical analysis based on hermeneutical phenomenology, general classification, and psychological and pedagogical approaches aimed at providing a sound multicultural education for Goryeoin children as well as other ethnic students.Results and conclusion. The curriculum and fruitfulness of Saena lSchool have been established to be one of the most effective multicultural educations in South Korea under the leadership of the school's principal, Pastor Cheon-Young Lee, who has excellent insight into the reasons for the emergence of Goryo people in South Korea. This study will show that his view of Korean history, which could persuade almost anyone, was the driving force behind his overcoming the numerous tough situations currently confronting the Korean educational environment, garnering love and respect from many Koreans, and bringing about remarkable innovation in education.